Assessment of submandibular sialolithiasis with panoramic and occlusal radiographs: diagnostic relevance in a clinical case - Bachtiar, Nini Andriyani; Yunus, Barunawaty; Gazali, Mohammad (Ikatan Radiologi Kedokteran Gigi Indonesia, 2025)
Objectives: This case report aims to describe the radiographic appearance of sialolithiasis on occlusal and panoramic radiographs. Case Report: A 27-year-old female patient came to RSGMP UNHAS with complaints of a lump under her right tongue. Before the lump appeared, the patient complained of pain under his right tongue. The swelling began approximately one week ago, initially about the size of a green bean. It has progressively increased in size until the present time. On occlusal radiography imaging, an irregular round radiopaque focus was found, and on panoramic radiography of the right mandibula zone, a well-defined radiopaque image in the form of an elongated oval/cylindrical shape was found. Case management: After clinical examination and panoramic and occlusal radiographs, a sialolithectomy was performed under general anesthesia in the right sublingual area. Conclusion: This case report is to describe radiographically the appearance of sialolithiasis on panoramic radiographs and occlusal radiographs, which is clearly visible in this case. Keywords: Radiography, panoramic; salivary glands; sialolithiasis; submandibular gland